2022
DOI: 10.1101/2022.05.16.22275165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unmet dental needs in children following suspension of school-based oral health services due to COVID-19

Abstract: Background: Children with dental caries (tooth decay), the world's most prevalent noncommunicative disease, face severe negative impacts on health and quality of life. Methods: The CariedAway trial is a study of the non-inferiority of WHO-sponsored essential medicines when used in a pragmatic, school-based caries prevention model. We present data on severity of disease, evidence of traditional dental care, and the impacts of the COVID-19 pandemic on urgent needs of low-income, minority children in New York Cit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Approximately 1 in 4 of children participating in CariedAway had untreated disease at baseline (1 in 3 for the COVID-19 sample), and we previously showed that only 11% had pre-existing sealants at their time of enrollment 42 . Following treatment, the overall odds of dental caries decreased by approximately 20% in both study arms.…”
Section: Discussionmentioning
confidence: 85%
“…Approximately 1 in 4 of children participating in CariedAway had untreated disease at baseline (1 in 3 for the COVID-19 sample), and we previously showed that only 11% had pre-existing sealants at their time of enrollment 42 . Following treatment, the overall odds of dental caries decreased by approximately 20% in both study arms.…”
Section: Discussionmentioning
confidence: 85%